Percepción de los profesores sobre la influencia de la comunicación motivación participación y valores en el desempeño directoral en instituciones educativas estatales nivel secundaria de la ciudad de Iquitos 2019 - Cahuaza Shupingahua, Kely (2021)
The aim of the study was to explain the influence of communication, motivation, participation and values on the principals’ performance in the different public high schools in the city of Iquitos - 2019. The research design for this study was an explanatory one and contemporary, multivariate, and transversal fieldwork design. The population was 365 teachers from public high school in the city of Iquitos, this research was based on stratified random sampling with proportional allocation of 188 teachers of 13 educative institutions. Data was collected through a survey and questionnaire were analyzed and validated by experts in the subject, and, with a reliability coefficient (principals’ performance with a 84,5% and independent variables, 96,1% approximately). The result shows that 50.5% of teachers have an inadequate perception of both verbal and written communication in the process of performance as principals in their educative institutions. Furthermore, 53.2% of the teachers are lack motivation on the part of the principals in their duties as principals in their educational institutions where they work. On the other hand, 51.1% of the teachers see an active participation of the actors in their duties as principals in their educational institution where they work and 52,7% of the teachers see an inadequate practice of values of the actors in their educational institutions where they work. Finally, 52.1% of teachers see that the principals do not achieve in terms of their performance as principals in their educational institutions that they lead. The bivariate analysis shows that: communication, motivation, participation and values are significantly associated with their performance as principals. (p-value <0,05) and in multicausal analysis leads us to the conclusion that communication, motivation, participation and values influences to the performance of the principals in their educational institutions significantly. (p-value<0.05).